2005
DOI: 10.4049/jimmunol.175.9.6177
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Enhances the Net Angiogenic Activity and In Vivo Growth of Human Non-Small Cell Lung Cancer in SCID Mice through Promoting CXCR-2-Dependent Angiogenesis

Abstract: In this study, we examined the biological action of IL-17 on human non-small cell lung cancer (NSCLC). Although IL-17 had no direct effect on the in vitro growth rate of NSCLC, IL-17 selectively augmented the secretion of an array of angiogenic CXC chemokines, including CXCL1, CXCL5, CXCL6, and CXCL8 but not angiostatic chemokines, by three different NSCLC lines. Endothelial cell chemotactic activity (as a measure of net angiogenic potential) was increased in response to conditioned medium from NSCLC stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
291
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(314 citation statements)
references
References 59 publications
(54 reference statements)
20
291
0
3
Order By: Relevance
“…We have clearly demonstrated that the established tumor progression was significantly diminished in IL-17 À/À mice, due to a decrease of angiogenesis. Consistent with this finding, prior studies have shown that substantial IL-17 expression levels in human cancer tissues were correlated with increased vascularity [4,5]. Moreover, our findings are consistent with other reports that IL-17 directly influenced on the proliferation and survival of tumor cells and that IL-6-STAT3 pathway promoted tumor growth in IL-17-dependent manner [34,43].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…We have clearly demonstrated that the established tumor progression was significantly diminished in IL-17 À/À mice, due to a decrease of angiogenesis. Consistent with this finding, prior studies have shown that substantial IL-17 expression levels in human cancer tissues were correlated with increased vascularity [4,5]. Moreover, our findings are consistent with other reports that IL-17 directly influenced on the proliferation and survival of tumor cells and that IL-6-STAT3 pathway promoted tumor growth in IL-17-dependent manner [34,43].…”
supporting
confidence: 93%
“…It has been demonstrated that IL-17 is expressed in tumor microenvironments [3][4][5]. The precise role of IL-17 during tumor development, however, remains unclear.…”
Section: Il-17 Promotes Tumor Development By Enhancing Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In so doing, TGF-β engages IL-17 production, important in defense against extracellular bacterial pathogens, but now linked to tumorigenesis. Functionally, over-expression of IL-17 in tumor sites correlated with recruitment of phagocytes, along with increased angiogenesis [16]. Recognized for its ability to induce cytokines, chemokines, colony stimulating factors and pro-angiogenic factors in multiple cell types, IL-17 enhanced tumor vascularity was inhibitable by CXCR2 neutralization [16].…”
Section: Tgf-β In Immune Dysregulationmentioning
confidence: 99%